Bioorthogonal Fluorescence Turn-On Labeling Based on Bicyclononyne-Tetrazine Cycloaddition Reactions that Form Pyridazine Products - Siegl, Sebastian J; Galeta, Juraj; Dzijak, Rastislav; Dračínský, Martin; Vrabel, Milan (ChemPlusChem, 2019)
Fluorogenic bioorthogonal reactions enable visualization of biomolecules with excellent signal-to-noise ratio. A bicyclononyne-tetrazine ligation that produces fluorescent pyridazine products has been developed. In stark contrast to previous approaches, the formation of the dye is an inherent result of the chemical reaction and no additional fluorophores are needed in the reagents. The crucial structural elements that determine dye formation are electron-donating groups present in the starting tetrazine unit. The newly formed pyridazine fluorophores show interesting photophysical properties the fluorescence intensity increase in the reaction can reach an excellent 900-fold. Model imaging experiments demonstrate the application potential of this new fluorogenic bioorthogonal reaction.
Keywords: Cycloaddition Reaction; Diels-Alder reactions; cyclic alkynes; Humans; cycloaddition reactions; fluorogenic probes; Microscopy, Confocal; můstkové bicyklické sloučeniny; Pyridazines; heterocyklické sloučeniny monocyklické; konfokální mikroskopie; pyridaziny; lidé; fluorescenční barviva; Fluorescent Dyes; Bridged Bicyclo Compounds; Heterocyclic Compounds, 1-Ring; nádorové buněčné linie; cykloadiční reakce; Cell Line, Tumor; tetrazines